Fungi in Mangrove: Ecological Importance, Climate Change Impacts, and the Role in Environmental Remediation - Juliana Britto Martins de Oliveira; Dario Corrêa Junior; Cláudio Ernesto Taveira Parente; Susana Frases (Microorganisms)
Mangroves are coastal ecosystems of great ecological importance, located in transition areas between marine and terrestrial environments, predominantly found in tropical and subtropical regions. In Brazil, these biomes are present along the entire coastline, playing essential environmental roles such as sediment stabilization, coastal erosion control, and the filtration of nutrients and pollutants. The unique structure of the roots of some mangrove tree species facilitates sediment deposition and organic matter retention, creating favorable conditions for the development of rich and specialized biodiversity, including fungi, bacteria, and other life forms. Furthermore, mangroves serve as important nurseries for many species of fish, crustaceans, and birds, being fundamental to maintaining trophic networks and the local economy, which relies on fishing resources. However, these ecosystems have been significantly impacted by anthropogenic pressures and global climate change. In recent years, the increase in average global temperatures, rising sea levels, changes in precipitation patterns, and ocean acidification have contributed to the degradation of mangroves. Additionally, human activities such as domestic sewage discharge, pollution from organic and inorganic compounds, and alterations in hydrological regimes have accelerated this degradation process. These factors directly affect the biodiversity present in mangrove sediments, including the fungal community, which plays a crucial role in the decomposition of organic matter and nutrient cycling. Fungi, which include various taxonomic groups such as Ascomycota, Basidiomycota, and Zygomycota, are sensitive to changes in environmental conditions, making the study of their diversity and distribution relevant for understanding the impacts of climate change and pollution. In particular, fungal bioremediation has gained significant attention as an effective strategy for mitigating pollution in these sensitive ecosystems. Fungi possess unique abilities to degrade or detoxify environmental pollutants, including heavy metals and organic contaminants, through processes such as biosorption, bioaccumulation, and enzymatic degradation. This bioremediation potential can help restore the ecological balance of mangrove ecosystems and protect their biodiversity from the adverse effects of pollution. Recent studies suggest that changes in temperature, salinity, and the chemical composition of sediments can drastically modify microbial and fungal communities in these environments, influencing the resilience of the ecosystem. The objective of this narrative synthesis is to point out the diversity of fungi present in mangrove sediments, emphasizing how the impacts of climate change and anthropogenic pollution influence the composition and functionality of these communities. By exploring these interactions, including the role of fungal bioremediation in ecosystem restoration, it is expected that this study would provide a solid scientific basis for the conservation of mangroves and the development of strategies to mitigate the environmental impacts on these valuable ecosystems.